Wajda i aktorzy - Guczalska, Beata (Przestrzenie Teorii, 2017)
Andrzej Wajda was one of those directors who created their actors in the way he allowed them to truly shape his films and theatre performances. The presence of his actors is striking in Wajda’s work, not only in the professional sense but also the human element. On numerous occasions Wajda emphasised that the only moment of true inspiration in his work is in the process of casting. While selecting actors he stayed extremely close to the characters, and in his quest for the right person he asked: “Who, in today’s social and existential situation, should play this character?” In his work he afforded his actors great freedom, which enabled them to develop their talents to the full. However, realising he could not always meet expectations with tried and tested actors, he sought out new faces and made radical changes to his team, which was often a source of frustration for actors. Aware of this lack of fulfillment, Wajda sometimes made it the subject of his films, sometimes returning to actors cast aside years earlier.